2011
DOI: 10.1111/j.1746-1049.2011.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Improving Infrastructure Quality on Business Costs: Evidence From Firm-Level Data in Eastern Europe and Central Asia

Abstract: Public infrastructure is one of the important determinants of economic growth. Not only access to but also quality of infrastructure affects firm productivity as well as people's livelihood. Frequent interruptions of the infrastructure-service supply impose extra backup costs on enterprises, hinder their timely business activities, and result in large losses of sales opportunities. This paper focuses on the impacts of improving the quality of public utilities (electricity, water supply, and telecommunications)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…For the formal business sector, studies have estimated the role of water as an input in manufacturing for developed economies where data are available (Reynaud, 2003;Dupont and Renzetti, 2001). More in line with this study, a number of papers have explored the effect of poor water infrastructure quality on formal firms, with mixed findings (Iimi, 2011;Moyo, 2011;Escribano et al, 2010;Bogetic and Olusi, 2013;Davis et.al, 2001). The literature on the effect of water infrastructure on firm performance is far limited relative to other business environment factors such as power infrastructure, access to finance and labor regulations (see for example Stel et al, 2007;Safavian and Sharma, 2009;Kaplan 2009, Alterido et al, 2011Fisher-Vanden et al 2015;Allcott et al, 2016).…”
Section: Introductionsupporting
confidence: 59%
“…For the formal business sector, studies have estimated the role of water as an input in manufacturing for developed economies where data are available (Reynaud, 2003;Dupont and Renzetti, 2001). More in line with this study, a number of papers have explored the effect of poor water infrastructure quality on formal firms, with mixed findings (Iimi, 2011;Moyo, 2011;Escribano et al, 2010;Bogetic and Olusi, 2013;Davis et.al, 2001). The literature on the effect of water infrastructure on firm performance is far limited relative to other business environment factors such as power infrastructure, access to finance and labor regulations (see for example Stel et al, 2007;Safavian and Sharma, 2009;Kaplan 2009, Alterido et al, 2011Fisher-Vanden et al 2015;Allcott et al, 2016).…”
Section: Introductionsupporting
confidence: 59%
“…Looking beyond the agricultural sector, Iimi (2011) finds that if all water supply disruptions could be removed in Europe and Central Asia, firms would on average be able to reduce their costs by 0.5%. This effect can be expected to be significantly larger in developing countries with less reliable water infrastructure.…”
Section: Higher-quality Water Infrastructure Matters For Firms' Produmentioning
confidence: 99%
“…The study used firm-level data collected from 26 European and Asian countries through interview of firms' managers to get their perception of whether regular availability of water has an impact on their firms' cost of operation and productivity. It was found that if the incidences of poor water supply are removed completely, firms are estimated to savemore of their operating costs especially those in the manufacturing, construction and hospitality industries thereby increasing their productivity and profitability (Limi, 2011). Switching focus to strictly developing countries, Islam & Hylan (2018) investigated the effects of unreliable water supplies on the productivity of manufacturing firms.…”
Section: Review Of Studies In the Physical Infrastructure Groupmentioning
confidence: 99%
“…Based on the review also, three research gaps were identified: methodological, theoretical and geographical research gaps. For the methodological gap, majority of the studies reviewed adopted the use of closed-ended questionnaires as the instruments for data collection (Islam & Hylan, 2018;Effiom & Edet, 2018;Bbaale, 2018), only two used interview method (Limi, 2011;Okoli et al, 2010). None of the studies used a combination of both questionnaire and interview methods.…”
Section: A Summary Of Empirical the Findingsmentioning
confidence: 99%
See 1 more Smart Citation